THE EFFECT OF BEETROOT BISCUITS (Beta vulgaris) ON THE HEMOGLOBIN LEVEL OF PATIENTS WITH PULMONARY TUBERCULOSIS - Amila Amila; Evarina Sembiring (The Indonesian Journal of Public Health, 2021)
hemoglobin levels in patients with pulmonary tuberculosis. This study aimed to examine the effect of beetroot biscuits consumption on the increase of hemoglobin levels in patients with pulmonary tuberculosis at the Integrated Service Unit of the Pulmonary Central Hospital of North Sumatera. The research design was quasi experimental  and used pre-tests and post-tests without a control approach. This study was conducted with a sample of 100 patients selected using the purposive sampling technique. Firstly, the hemoglobin level of the patients was measured. Then, beetroot biscuits were given to the patients for thirty days as the intervention. A Wilcoxon test was performed to pinpoint the differences between the pre-test and post-test results. It was found that there was a 2.01 gr/dl increase in hemoglobin after beetroot biscuits were given to patients with pulmonary tuberculosis at the Integrated Service Unit of the Pulmonary Central Hospital of North Sumatera. It was also found that the differences were significant when comparing the average level of hemoglobin before and after the intervention with a p value of 0.000. This study suggests that doctors and nurses play important roles in constructing patients’ knowledge and understanding on the importance of anemia prevention in order to improve community knowledge to use local resources to improve health outcomes.Keywords: anemia, biscuit, beetroot, tuberculosis